The Impact of Using Digital Wallets on Generation Z's Consumptive Behavior - Amanda, Sri Anita; Putri, Ananda; Achsana, Andi Devi; Magfirah, Sri Uya; Hasan, Muhammad (International Journal of Management and Business Intelligence, 2023)
Digital wallets (e-wallets) are digital financial products that are considered a more efficient alternative to payments cash. Electronic money is usually stored in digital wallets to make transactions easier. Today's digital wallets provide benefits, convenience and efficiency in payment transactions, making it easier for generation Z to spend their money, thereby influencing their consumer behavior as well. Research shows that digital wallets have a significant impact on generation Z consumer behavior. Digital wallets are convenient, safe, efficient and innovative for generation Z retail transactions, especially in online deliveries, grocery orders and e-commerce transactions.